The impact of R&D strategies on the performance of new product development with emphasis on the role of R&D team performance (case study: Hooshmand Sazeh Arvin Ara Corporation). (16th May 2019) - Aghdam, Siamak Ghorbanian; Nikabadi, Mohsen Shafiei; Ebrahimi, Seyyed Abbas
The main goal of the paper is to study the effect of research and development strategies on performance of new product development with emphasis on the role of research and development team in Hooshmand Sazeh Arvin Ara Company. This is an applied research and has done as a survey, cause-effect research. In this research, confirmatory factor analysis, correlation test, and path analysis were used. In this survey, a questionnaire included 37 items has been distributed among 160 technicians, research and development, production and marketing experts of Houshmand Sazeh Arvin Ara Company. The innovation of this research is to examine the impact of these three variables in a single, general conceptual model. Findings of correlation show meaningful and positive relationship between model variables and indicate that research and development strategies contribute to performance of new product development that this influence is more when there is research and development team.